How the Uniqueness of the Radical Populist Right in Latin America Allows Us to Rethink the Global Radical Populist Right - Ubilluz, Juan Carlos (2024)
This article studies the rise of PRR (populist radical right) candidates in Brazil, Chile, Costa Rica, and Peru. It focuses on political processes and campaign issues in order to determine the singularity of the PRR in Latin America. From there, an attempt is made to arrive at a broader (and more global) definition of the PRR than that of Cas Mudde, the most important academic in far-right studies. For Mudde the central triad of the PRR’s ideology is nativism, authoritarianism, and populism. The Latin American PRR is indeed authoritarian and populist, but it is less oriented toward anti-immigration nativism than towards the defense of the heterosexual family against “gender ideology”. This is why the author proposes to alter Mudde’s triad in the following manner: social conservatism, authoritarianism, and populism. On the other hand, while the European and American PRR discursively opposes neoliberalism, the Latin American PRR sticks to the defense of the “economic model”. But this singularity reveals the hidden truth of the PRR in the West and perhaps in the world: namely, that far from constituting a way out of neoliberalism, the PRR sustains it by displacing popular discontent with the system toward the hatred of the immigrant, religious or sexual Other. This is why it is also proposed to include economics in the definition of the PPR so as to finally arrive at the tetrad: neoliberalism, social conservatism, populism and authoritarianism.